PROGRAM PENDAMPINGAN LATIHAN FISIK: PENINGKATAN KUALITAS ATLET TENIS MEJA CLUB PERSATUAN TENIS MEJA APC - Putu Diah Asrida; I Gede Agus Adi Saputra (Sewagati, 2024)
The community service program which takes the title Physical Training Assistance: Improving the Quality of Table Tennis Athletes of the APC Table Tennis Association Club, is an activity that aims to improve the physical performance of table tennis athletes through targeted and measurable physical exercise. This program involves professional physical trainers who provide intensive assistance to athletes in improving strength, endurance, agility and reaction speed which are important aspects of table tennis. In addition, the program also educated local coaches and the community on the importance of physical training in supporting technical performance and reducing the risk of injury. The results of the program showed significant improvements in the physical aspects of athletes, with improvements in muscle strength, endurance, and agility that had a direct impact on on-court performance. The program also reduced the risk of injury through the application of proper warm-up techniques and educational exercises. The education provided succeeded in increasing the understanding of coaches and athletes about the importance of physical components in athlete development. The sustainability and replication of this program is expected to support the achievements of table tennis athletes in national and international competitions